Frequency Agile Radial-Shaped Varactor-Loaded Reflectarray Cell - Venneri, Francesca; Costanzo, Sandra; Di Massa, Giuseppe; Borgia, Antonio; Raffo, Antonio (Společnost pro radioelektronické inženýrství, 2016)
An equivalent circuit approach is adopted in this paper to analyze a novel varactor loaded phasing line, specifically designed to improve the frequency agility features of reconfigurable aperture-coupled reflectarray cell, through the use of a couple of microstrip radial stubs. The proposed analysis method is fruitfully implemented to perform a fast and preliminary investigation on the improvements provided by the radial shaped phasing line in terms of frequency agility of the reflectarray unit cell. The method is adopted to compare frequency performances of radial and linear phasing line geometries, allowing to effectively demonstrate the radial line geometry contribution to the enhancement of the unit cell frequency performances.
Keywords: Microstrip radial line; varactor; reflectarray.